THE ROLE OF HEARING AND LISTENING IN THE PERFORMER OF CLASSICAL MUSIC - SZlLAGYI, Ana (Studia Universitatis Babes-Bolyai Musica, 2026)
The paper aims to highlight the role of hearing and listening in the performance of classical music, an aspect that the interpreter must be aware of. Being busy with the visual aspect (if the piece is played with score) or stressed playing by heart, besides mastering technical difficulties, the interpreter partially neglects hearing, the essence of music. The interpreter has to deal with the listening by an audience. For this, he / she must know some acoustic and cognitive laws, how the hearing generally works, and how to convey a message through the performance. Moreover, he / she has to hear in advance, in his inner hearing the sounds he / she are going to play. During the play, the interpreter has also to listen to what he / she is playing or singing, and rectify or increase the sound quality, if it is not satisfactory.